High Throughput Sequencing for the Detection and Characterization of RNA Viruses - Fitzpatrick, Amy H.; Rupnik, Agnieszka; O'Shea, Helen; Crispie, Fiona; Keaveney, Sinéad; Cotter, Paul (Frontiers in Microbiology, 2021)
This review aims to assess and recommend approaches for targeted and agnostic High Throughput Sequencing of RNA viruses in a variety of sample matrices. High Throughput Sequencing has much to offer to the field of environmental virology as its increased sequencing depth circumvents issues with cloning environmental isolates for Sanger sequencing. That said however, it is important to consider the challenges and biases that method choice can impart to sequencing results. Here, methodology choices from RNA extraction, reverse transcription to library preparation are compared based on their impact on the detection or characterisation of RNA viruses.